Risk assessment candidates for carbon dioxide-related internal browning of apple during controlled atmosphere storage - McTavish, Christine; Klarer, Emmi; Milne, Shae; Valdez, Natalie; Mattheis, James; Leisso, Rachel; Rudell, David (Postharvest biology and technology, 2025)
Internal browning of apple (Malus domestica Borkh.) associated with high respiration and pCO2 continues to contribute to annual losses of many economically important cultivars in most growing regions worldwide. This effort sought to determine metabolites that change with storage conditions factors and, consequently, infer relative risk. To accomplish this, internal browning was triggered in 5 cultivars using high pCO2 and ultra-low pO2 conditions, coupled with diphenylamine drenching to verify if elevated pCO2 was a contributing factor. From this, the metabolic fingerprints of symptomatic and asymptomatic cortex were compared on all 5 cultivars. Levels of metabolites altered by symptom development in multiple cultivars were then monitored in ‘Fuji’ asymptomatic cortex prior to and during symptom development in apples stored in a range of pCO2 revealing metabolites that were associated with high-risk storage conditions followed by symptom development. These included elevated levels of lipids such as acylated steryl glycosides, free fatty acids, sphingolipids, diglycerides, and unknowns likely produced from α-tocopherol. Metabolite levels that diminished with risk included steryl esters and select amino acids. Relationships between candidate metabolite levels and risk conditions are expected to remain robust with the tested cultivars and, potentially, other susceptible cultivars. Whether other production variables impacting risk of internal browning are represented by the same metabolic changes is the subject of continued investigations with the goal of developing tests indicative of compromised fruit before symptoms appear. •Cortex metabolic fingerprint of 6 apple cultivars is altered by internal browning.•Levels of some symptom-associated metabolites change prior to symptom development.•Tracking metabolites linked with IB may be a basis for risk assessment.